3D Fluid Flow and Heat Transfer Simulation of Turbulent Flow over Bank of Tubes - Motasim Shalgoum; Akram Abdullah Alharari; Talal Albireeshni; Alhosain Abdelhameed (Surman Journal of Science and Technology, 2024)
This study presents a simulation of the effect of different parameters on the performance of a bank of tubes. A CFD simulation of a 3D steady state turbulent flow over a bank of tubes was designed and analyzed using ANSYS fluent 19.0. The effect of cross-wise and stream-wise pitches of 1.25D, 1.5D, 1.75D and 2D as well as diameters of 1cm, 1.5cm, 1.75cm and 2cm on the heat transfer coefficient and skin friction coefficient of the tube were studied and analyzed for both inline and staggered configurations. Results have shown that the cross-wise and stream-wise pitches and tube diameters have a noticeable effect on the performance of the tube bank for both in line and staggered configuration. Results have also shown that the staggered configuration had a better thermal performance than inline configuration.